Per(sino)ficação - Carvalho, Fabio; Schiavoni, Flávio Luiz; Araújo, João (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
The bell’s culture is a secular tradition strongly linked to the religious and social activities of the old Brazilian’s villages. In São João del-Rei, where the singular bell tradition composes the soundscape of the city, the bell’s ringing created from different rhythmic and timbral patterns, establish a language capable of transmitting varied types of messages to the local population. In this way, the social function of these ringing, added to real or legendary facts related to the bell’s culture, were able to produce affections and to constitute a strong relation with the identity of the community. The link of this community with the bells, therefore transcends the man-object relationship, tending to an interpersonal relationship practically. Thus, to emphasize this connection in an artistic way, it is proposed the installation called: PER (SINO) FICAÇÂO. This consists of an environment where users would have their physical attributes collected through the use of computer vision. From the interlocking of these data with timbral attributes of the bells, visitors would be able to sound like these, through mapped bodily attributes capable of performing syntheses based on original samples of the bells. Thus the inverse sense of the personification of the bell is realized, producing the human “bellification”.